Development and Design of Portable 1 Phase Spot Welding Machine - Kurniawan, Ipung; Pujono, Pujono; Pribadi, Joko Setia; Prabowo, Dian (Universitas Sultan Ageng Tirtayasa, 2025)
The design method used as an approach in designing portable spot welding machines is the VDI 2222 design method. Working drawings use ISO standards and the design application used is solidworks. From the design method used as an approach in designing portable spot welding machines, the results of image documents in the form of working drawings are obtained which will then be used in the production process. The result of maximum stress calculation result of the frame used is 0,301 N/mm2 ≤ ????izin = 166,67 N/mm2, therefore the results obtained show that the elbow profile size 40 mm x 40 mm x 2 mm is confirmed to be safe to withstand the given load. The spring calculation above τ max = 27,07 Kg/mm2 ≤ τa = 65 Kg/mm2, therefore the results obtained show that the spring with a winding diameter of 7 mm and a wire diameter of 1.2 mm is certainly safe to withstand the given load